NATIONAL DEFESE AND DEVELOPMENT: DIALOGUES BETWEEN THE MEANING OF HÉLIO JAGUARIBE’S “AUTONOMY” CONCEPT AND THE NATIONAL STRATEGY OF DEFENSE - Nogueira da Gama, Pedro (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
In his studies on development, international relations and national defense issues, political scientist Hélio Jaguaribe reflected on Brazil’s “autonomy” since the country is inserted in the interstate capitalist system. First approved in 2008, the National Defense Strategy was created with the aim of promoting a modernization of the Brazilian defense structure. This article proposes to understand the meanings of “autonomy” in the strategic thinking of Jaguaribe. In addition, it presents a potential dialogue between his formulations and the guidelines of the National Defense Strategy in its different versions.